2006
DOI: 10.1303/aez.2006.339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pollen of transgenic rice line, TT9-3 with a fused cry1Ab/cry1Ac gene from Bacillus thuringiensis Berliner on non-target domestic silkworm, Bombyx mori Linnaeus (Lepidoptera: Bombyxidae)

Abstract: Some cry genes from Bacillus thuringiensis Berliner (Bt) have been transferred into rice plants for resistance to lepidopterans. The ecological risks of Bt rice, especially the non-target effects of Bt rice pollen on the domestic silkworm, Bombyx mori Linnaeus in mulberry-rice mixed cropping area should be clarified cautiously. In light of B. mori fully domesticated and not surviving independently in the field, a series of laboratory bioassays were conducted to evaluate the effect of the pollen from an indica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The culture of the silkworm Bombyx mori is an important export industry that provides considerable income for people in many temperate Asian countries [22]. However, B. mori is susceptible to Cry1Ac and Cry2Ab proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The culture of the silkworm Bombyx mori is an important export industry that provides considerable income for people in many temperate Asian countries [22]. However, B. mori is susceptible to Cry1Ac and Cry2Ab proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Existing results show that Bt toxins have no lethal effect on the two insects. Few studies of the sublethal effects of Bt toxins on A. mellifera [18], [20], [26], [27] and B. mori [22], [23], [28] have been conducted either. However, as well as the side effects of pesticides on beneficial arthropods [29][31], the sublethal effects of Bt toxins on these two economically important insects might negatively impact larval development and immune capacity and lead to colony population decrease [31].…”
Section: Introductionmentioning
confidence: 99%
“…It is also the representative non-target insect of pesticide [38,39]. Pesticide toxicology of silkworm is required for pesticide registration in China.…”
Section: Using Silkworm As a Target For Biological Safety Evaluation mentioning
confidence: 99%
“…This measure would decrease the direct exposure of silkworms to maize pollen. In this respect, Yao et al (2006) conducted a series of laboratory bioassays to evaluate the effect of the pollen from a GM rice line with a fused cry1Ab/cry1Ac gene on silkworms. No significant adverse effects were observed on the survival, growth and development of silkworm young larvae, even after the neonates had been exposed to Bt pollen at the highest density of 3,395.0 grains/cm 2 for 48 h.…”
Section: Vii) Potential Adverse Effects Of Mon810 Maize On Non-targetmentioning
confidence: 99%
“…Yao et al (2006) concluded that Bt rice pollen pose little effect on silkworm rearing in natural settings. Taking into account the available literature data, the GMO Panel is of the opinion that the risk of MON810 pollen to silkworm and other non-target lepidopteran species is negligible due to its low CRY1Ab content and the low levels of exposure of wild species to maize pollen.…”
Section: Vii) Potential Adverse Effects Of Mon810 Maize On Non-targetmentioning
confidence: 99%